Malawi Agricultural Sector Risk Assessment - Giertz, Asa; Caballero, Jorge; Galperin, Diana; Makoka, Donald; Olson, Jonathan; German, George (World Bank, Washington, DC, 2016)
With more than three-quarters of its workforce employed in agriculture, Malawi is highly vulnerable to any adverse events affecting the agriculture sector, and agricultural risks are ever present in the country. Agricultural risks can obstruct development and enforce poverty traps, particularly for a country as reliant on agriculture as Malawi. Because of the size of the sector in the economy and the importance of agricultural products for export, agricultural growth correlates closely with gross domestic product (GDP) growth. Malawi’s effort to manage risks and to provide relief in response to adverse events diverts significant resources from longer-term development investments. To better understand the dynamics of agricultural risks and identify appropriate responses, incorporate an agricultural risk perspective into decision making, and build the capacity of local stakeholders in risk assessment and management, the agricultural risk management team (ARMT) of the agriculture and environment services department of the World Bank conducted an agriculture sector risk assessment. The purpose of this report is to assess existing agricultural risks, prioritize them according to their frequency and impacts on the sector, and identify areas of risk-management solutions that need deeper specialized attention. Three levels of risks were assessed: production risks, market risks, and enabling environment risks to selected supply chains. The report takes a quantitative and qualitative approach to assessing risk. This report is structured as follows: chapter one gives introduction and context. Chapter two provides an overview of the agriculture sector and the selected crops. Chapter three maps the production, market, and enabling environment risks to food crops and export crops. Chapter four looks at the adverse impacts of agricultural risks in terms of losses, both at the national level and for different regions. Chapter five prioritizes the risks in terms of their frequency and the severity of their impacts, and discusses solutions based on this prioritization, ongoing risk-management activities, and the feedback from the consultative workshop.